Effects of Vitamin D and Calcium Treatment on Morphological and Metabolic Changes in Bone Tissue After Ovariectomy: Efectos del tratamiento con vitamina D y calcio sobre los cambios morfológicos y metabólicos del tejido óseo tras la ovariectomía - Dzholdosheva, Gulai; Sattarov, Absamat; Shatmanov, Suinali; Omurzakova, Gulnara; Tashieva, Ainura (Gaceta Médica de Caracas, 2025)
Introduction: Osteoporosis is a major public health issue, especially among postmenopausal women. Objective: This study seeks to explore metabolic and morphological alterations in bone tissue following experimental ovariectomy and to evaluate the roles of vitamin D and active calcium in correcting these changes. Method: 26 sexually mature female rats were used, which, after ovariectomy, were divided into two cohorts: one underwent pharmacological treatment. Morphological examination of tissues and biochemical tests were used to assess changes in hormone concentration in blood plasma. Result: The data demonstrate that on the 30th day after rats’ ovariectomy, there was a marked thinning of trabecular (bone beam) structures and the presence of inflammatory foci within Haversian canals.